DETERMINAN PROFITABILITAS SUB SEKTOR PERBANKAN DENGAN INFLASI SEBAGAI VARIABEL MODERASI - B2041151008, DIAGO RINGGA MONIAGA (Equator Journal of Management and Entrepreneurship (EJME), 2019)
Economic development in Indonesia is very dependent on development and contribution of the banking sector. The banking sector which has more capital is seen by other financial institutions, its performance and cash flow is fast, the community is relatively chosen to overcome capital difficulties.The purpose of this study was to analyze the development of the financial performance of the banking industry in Indonesia and to determine the effect of microeconomic and macroeconomic variables on the financial performance of banks with inflation as a moderating variable. The analytical tool used is descriptive analysis and path analysis using SPSS software.The results of the research obtained by CAR variable have a significant and positive effect on the variables of Indonesian banking financial performance. Economic growth has a significant and positive effect on Indonesia's banking financial performance. Inflation has significant and negative effect on the profitability variable. Inflation variables indirectly, positively and significantly influence the variable of Indonesian banking financial performance through CAR with a value of -0.302, while the inflation variable has an indirect, negative, and significant effect on Â the variables of Indonesian banking financial performance through economic growth with a value of -0.258Â Keywords : Bank, Bank performance, finance, inflation